2018
DOI: 10.1063/1.5015959
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultraviolet photo-response in Dy doped ZnO thin film

Abstract: In the present work, a Dy doped ZnO thin film deposited by the spin coating method has been studied for its potential application in a ZnO based UV detector. The investigations on the structural property and surface morphology of the thin film ensure that the prepared samples are crystalline and exhibit a hexagonal crystal structure of ZnO. A small change in crystallite size has been observed due to Dy doping in ZnO. AFM analysis ascertains the grain growth and smooth surface of the thin films. The Dy doped Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Figure 7b–d shows the Tauc plot of Eu 2− x Fe x Ti 2 O 7 (for x = 0.0, 0.1, 0.2), assuming direct transition in between conduction and valence band. [ 58 ] The energy bandgaps ( E g ) were determined from the relation [ 58–60 ] αhν=Afalse(hνEnormalgfalse)nwhere n = 1/2 corresponds to an allowed direct electronic transition. From Figure 7b–d, it has been observed that Eu 2− x Fe x Ti 2 O 7 has multiple bandgaps.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7b–d shows the Tauc plot of Eu 2− x Fe x Ti 2 O 7 (for x = 0.0, 0.1, 0.2), assuming direct transition in between conduction and valence band. [ 58 ] The energy bandgaps ( E g ) were determined from the relation [ 58–60 ] αhν=Afalse(hνEnormalgfalse)nwhere n = 1/2 corresponds to an allowed direct electronic transition. From Figure 7b–d, it has been observed that Eu 2− x Fe x Ti 2 O 7 has multiple bandgaps.…”
Section: Resultsmentioning
confidence: 99%
“…These elements present excellent physicochemical properties based on the electronic transitions occurring within the 4f energy shell [ 16 ]. As a result, their high conductivity, magnetic, electrochemical, and luminescent properties enabled their effective use as photocatalysts [ 17 ], photodetectors [ 18 ], Schottky diodes [ 19 ], and UV detectors [ 20 ], to cite only a few. Moreover, rare-earth compounds have been proved as promising candidates for improving gas sensing performance owing to their catalytic nature, fast oxygen ion mobility, and high surface basicity [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To realize high-performance deep-UV optoelectronic devices, great efforts have been devoted to studying doped ZnMgO [ 25 ], such as Dy [ 26 ], Ag [ 27 ], Al [ 28 ], Ga [ 29 ], and As [ 30 ]. Among these elements, Ga is the most effective n-type dopant in ZnO ascribing to the covalent bond length of Ga-O (1.92 Å) is similar to that of Zn-O (1.97 Å).…”
Section: Introductionmentioning
confidence: 99%